2017
DOI: 10.1371/journal.pone.0183441
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of incorporating fertility control into typical culling regimes in wild pig populations

Abstract: Effective management of widespread invasive species such as wild pigs (Sus scrofa) is limited by resources available to devote to the effort. Better insight of the effectiveness of different management strategies on population dynamics is important for guiding decisions of resource allocation over space and time. Using a dynamic population model, we quantified effects of culling intensities and time between culling events on population dynamics of wild pigs in the USA using empirical culling patterns and data-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 59 publications
3
37
0
1
Order By: Relevance
“…Conception probability was density dependent such that conception did not occur in individuals in grid cells that were already at carrying capacity. The population-level host demographic dynamics were similar to a logistic model (Pepin et al 2017).…”
Section: Methodsmentioning
confidence: 73%
“…Conception probability was density dependent such that conception did not occur in individuals in grid cells that were already at carrying capacity. The population-level host demographic dynamics were similar to a logistic model (Pepin et al 2017).…”
Section: Methodsmentioning
confidence: 73%
“…Conception probability was density dependent such that conception did not occur in individuals in grid cells that were already at carrying capacity. The population-level host demographic dynamics were similar to a logistic model (Pepin, Davis, Cunningham, VerCauteren, & Eckery, 2017).…”
Section: Birth and Death Parametersmentioning
confidence: 75%
“…) and fertility control (see Pepin et al. , b for theoretical evaluation). These are investments that have not yet been realized in terms of feral swine removals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous work has shown that prioritizing removals during non‐birthing periods can improve the efficiency of control (Pepin et al. , b), suggesting that further optimization of timing could be helpful. However, our results are national‐scale averages and previous work has indicated that forage availability can greatly impact feral swine population growth and establishment (Tabak et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation